Modeling of photovoltaic systems using Modified Elephant Swarm Water Search Algorithm. (1st November 2020) - Mandal, Sudip
ABSTRACT: A highly accurate modeling of photovoltaic (PV) systems from experimental data is a very important task for electronic engineers for efficient design of PV systems. Suitable optimization techniques are required for this kind of computational modeling. In this work, a Modified Elephant Swarm Water Search Algorithm (MESWSA) has been proposed for efficient and accurate estimation of the parameters of solar cells and PV modules. Initially, the algorithm was tested on two different benchmark PV systems, i.e. a solar cell and PV module using the single-diode model and the double-diode model. The experimental results and comparisons with some other optimization technique clearly reveal the effectiveness of this proposed algorithm in terms of the accuracy of final solutions, success rate, convergence speed, and stability. Next, the proposed MESWSA optimization technique has also been tested against the manufacturer's datasheet of two industrial solar modules. Results show the efficiency of MESWSA algorithm for I-V characteristics of solar modules at different operating conditions. Therefore, this MESWSA can serve as a new alternative metaheuristic for parameter estimation of solar cells/PV modules. Abbreviations: Modified Elephant Swarm Water Search Algorithm (MESWSA) Photovoltaic (PV)